2021
DOI: 10.1371/journal.pone.0252440
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 pneumonia on chest X-rays: Performance of a deep learning-based computer-aided detection system

Abstract: Chest X-rays (CXRs) can help triage for Coronavirus disease (COVID-19) patients in resource-constrained environments, and a computer-aided detection system (CAD) that can identify pneumonia on CXR may help the triage of patients in those environment where expert radiologists are not available. However, the performance of existing CAD for identifying COVID-19 and associated pneumonia on CXRs has been scarcely investigated. In this study, CXRs of patients with and without COVID-19 confirmed by reverse transcript… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 35 publications
0
11
0
1
Order By: Relevance
“…The DLAD-10 has previously shown to have good performance in detecting the 10 clinically well-defined and important abnormalities, with AUROCS ranging 0.895-1.00 in CT-confirmed datasets [26]. Furthermore, the engine has shown good performance in COVID-19 patients [42][43][44]. The performance of the DLAD-10 is high because it has been trained and validated on large datasets, utilizing over three million images for pretraining and fine-tuning.…”
Section: Discussionmentioning
confidence: 99%
“…The DLAD-10 has previously shown to have good performance in detecting the 10 clinically well-defined and important abnormalities, with AUROCS ranging 0.895-1.00 in CT-confirmed datasets [26]. Furthermore, the engine has shown good performance in COVID-19 patients [42][43][44]. The performance of the DLAD-10 is high because it has been trained and validated on large datasets, utilizing over three million images for pretraining and fine-tuning.…”
Section: Discussionmentioning
confidence: 99%
“…The authors believed that DeepCOVID-XR is more reliable than the study by Murphy et al for predictions produced by DeepCOVID-XR are in line with the radiological diagnosis by a consensus of experts. Hwang et al [27] observed that DL-based CAD may improve the performance of readers, while the performance of nonradiologists significantly improved in the CADassisted interpretation. Furthermore, inter-reader agreement among physicians showed significant improvement when assisted with the CAD.…”
Section: Comparison Of the Diagnostic Performance Of DL And Ai Systems With Radiologistsmentioning
confidence: 99%
“…To increase the sensitivity and specificity of imaging patterns for pneumonia in CR, deep learning (DL) algorithms must become more prevalent. Prior studies have shown that the use of artificial intelligence (AI) significantly improves the detection of pneumonia in CR [ 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 ]. However, the number of relevant studies is comparatively low [ 11 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Prior studies have shown that the use of artificial intelligence (AI) significantly improves the detection of pneumonia in CR [ 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 ]. However, the number of relevant studies is comparatively low [ 11 , 16 ].…”
Section: Introductionmentioning
confidence: 99%